The differences of child feeding practices between working mothers and daycare staff in daycare - Setiyaningrum, Hanna Yuni; Fahmida, Umi; Anggorowati, Rita (World Nutrition Journal, 2024)
Child feeding practices between working mothers and daycare staff play an important role in children’s dietary intake. This study aims to compare child-feeding practices between working mothers and daycare staff. Additionally, the study explores the perspectives of working mothers, daycare staff, and management regarding their roles in child feeding practices to the children.